A preliminary study for early breast cancer detection with microwaves - Emine Avşar Aydin (Tehnički Glasnik, 2018)
Breast cancer is the most common type of cancer in female all over the world. Early detection and treatment gives a chance to overcome this cancer. In breast cancer detection, there are many methods such as X-ray mammography, Magnetic Resonance Imaging, and Ultrasound Imaging. However, existing these methods have limitations such as X-rays, disturbing pressure on the breast, and high cost of devices, etc. Because of all the reasons mentioned, microwave breast imaging has the potential to overcome from some of the limitations of conventional breast cancer screening systems. The physical basis breast cancer detection by microwaves depends on the difference between the dielectric properties of normal and malignant breast tissue. Microwave breast cancer imaging is also a noninvasive method and it has low cost. Therefore, microwave imaging technology for breast cancer detection has attracted much attention by many researchers in these days. By using Computer Simulation Technology Microwave Studio and Antenna Magus Software, breast model with tumor and antennas were generated in this study. The presence of the tumor was investigated using a receiver and a transmitting antenna. While the transmitting antenna was stationary, the receiving antenna was moved to different positions. S11 (return loss) results were evaluated. This study is a preliminary study to determine the location and characteristic features of the tumor. Furthermore, this study will show that scanning methods will determine the location and size of the tumor at higher accuracy and the reconstruction of the reflected waves will allow to clearly determining the location of the tumor.